KECERDASAN EMOSIONAL DITINJAU DARI STRUKTUR KELUARGA DAN POLA ASUH ORANG TUA PARA SISWA SMA DI KABUPATEN BADUNG - Arsana, I Gusti Lanang Rai (Widyadari: Jurnal Pendidikan, 2019)
This study aimed at (1) finding out the difference in the level of emotional intelligence between the senior high school students who came from the extended family structure and those who came from the core family structure in Bandung regency. (2) finding out the difference in the level of emotional intelligence between the senior high school students in Badung regency who came from the extended family structure and those who came from the core family structure with both types of the families had an accepting attitude. (3) finding out the difference in the level of emotional intelligence between the senior high school students in Badung regency who came from the extended family structure and those who came from the core fsmily structure in which both types of family structure had a rejecting attitude. This study was conducted to the senior high school students in Badung regency and used an ex post facto research method with 2x2 factorial design which involved a sample of 395 students taken by a technique which combined probability and non-probability sampling or multi stage purposive random sampling. The independent variables in this study were family structure and child rearing  pattern. Each of the independent variables were divided into two,i.e., family structure  was split into extended family structure and core family structure, whereas child  rearing  pattern was split into child rearing pattern in which the parents had an accepting  attitude and child rearing pattern in which the parents had a rejecting attitude. The dependent variable was level of emotional intelligence. The study used questionnaires as the instruments to collect data, i.e., emotional intelligence questionnaire, family structure questionnaire and child rearing  pattern questionnaire. The data were analyzed by two-way ANOVA with Scheffe test.          The result shows thet (1) there was a difference in the level of emotional intelligence when it was viewed from the extended family structure and when it was viewed from the core family structure, (2) the was a difference in the level of emotional intelligence between the studets whose parents had an accepting attitude and those whose had a rejecting attitude both in the extended and core family structure and (3) there was a difference in the level of emotional intelligence between the students whose parents had a rejecting attitude and those whose parents both in the extended and core family stuctures.          The conclusion thet can be made from this study is that an extended family structure can increase a student,s emotional intelligence. In order to get a maximum result the child rearing patterns has to be considered in a family structure.